Penerapan Strategi Pembelajaran Berbasis Masalah dalam Pendidikan Agama Kristen di Era Disrupsi - Anastasia Runesi; Christian Yohanes; Putri Maria Juliana (SIKIP: Jurnal Pendidikan Agama Kristen, 2021)
The disruption era is a condition that is closely related to changes in the industrial world from the previous system. This era brings major changes in various fields of life because of the presence of technology that makes it easier and at the same time shifts the role of humans. The result is felt in all fields, including Christian religious education. Machines have replaced human tasks in a variety of actions that have caused humans to no longer be a resource that needs to be valued and employed. Responding to this problem, Christian Religious Education must be present as a means of growing faith and the character of Christ which can be a guide in facing and solving any problems in everyday life, including problems that arise in the era of disruption. This study aims to examine the relevance of problem-based learning strategies applied in Christian Religious Education learning as an answer to problems that occur in the era of disruption. The method used in revealing the relevance is descriptive qualitative. The results of the study indicate that the application of problem-based learning strategies in Christian Religious Education is relevant, effective, and efficient in responding to the challenges and needs in the era of disruption. This is because students will be equipped with soft skills so that they are able to solve problems creatively and innovatively but still adhere to the character of Christ. AbstrakEra disrupsi merupakan keadaan yang erat dengan perubahan pada dunia industri dari sistem sebelumnya. Era ini membawa perubahan besar pada berbagai bidang kehidupan karena hadirnya teknologi yang mempermudah sekaligus menggeser peranan manusia. Akibatnya sangat terasa dalam segala bidang, termasuk pendidikan Agama Kristen. Mesin telah menggantikan tugas manusia dalam berbagai macam tindakan yang menyebabkan manusia tidak lagi menjadi sumber daya yang perlu dihargai dan dipekerjakan. Menanggapi masalah itu, Pendidikan Agama Kristen harus hadir sebagai sarana menumbuhkan iman dan karakter Kristus yang dapat menjadi pedoman dalam menghadapi dan menyelesaikan masalah apapun di kehidupan sehari-hari termasuk permasalahan yang timbul di era disrupsi. Penelitian ini bertujuan untuk mengkaji relevansi strategi pembelajaran berbasis masalah yang diterapkan dalam pembelajaran Pendidikan Agama Kristen sebagai jawaban atas masalah yang terjadi di era disrupsi. Metode yang digunakan dalam mengungkap relevansi itu adalah kualitatif deskriptif. Hasil penelitian menunjukkan bahwa penerapan strategi pembelajaran berbasis masalah dalam Pendidikan Agama Kristen merupakan hal yang relevan, efektif, dan efisien menjawab tantangan serta kebutuhan di era disrupsi. Hal ini karena peserta didik akan diperlengkapi dengan soft skill sehingga mampu menyelesaikan masalah secara kreatif dan inovatif namun tetap berpegang dengan karakter Kristus.